HISTORY IN THE QUR'AN: THEMATIC TAFSIR ANALYSIS OF ITS VALUES AND FUNCTIONS: Sejarah dalam Al-Qur’an: Analisis Tafsir Tematik atas Nilai dan Fungsinya - Haula Teranggano; Ainur Rha’in (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
One-third of the Quran's content narrates history, proving that history holds a significant position in Islam. The purpose of this research is to delve deeper into the definition and urgency of the importance of history in Islam and how Islam views history as a whole. The method used in this research employs qualitative methods and a literature approach to obtain results from books and journals used as references. The general outcome can be seen in the Quranic verse Surah Al-Hashr, verse 18, which directs humans to reflect on the past to plan for the future. This is further emphasized in other surahs and verses that explain and provide benefits through the narration of the history of previous generations so that the current generation can take valuable lessons from it.